Microfluidic fabrication of stimuli-responsive microdroplets for acoustic and optical droplet vaporization. Issue 15 (5th April 2016) - Zhu, Zhiqiang; Wu, Qiang; Li, Guangbin; Han, Shuya; Si, Ting; Xu, Ronald X.
Abstract : We developed a flow-focusing microfluidic assay for fabricating stimuli-responsive microdroplets (SRMs) for imaging and therapeutic applications. Abstract : A droplet-based microfluidic flow-focusing system was developed for on-chip fabrication of stimuli-responsive microdroplets (SRMs) that underwent rapid liquid-to-gas phase transition and volume expansion upon external stimuli. Silver nanoparticles (SNPs) were suspended in perfluorocarbon (PFC) liquid and encapsulated in a lipid shell to form a SRM. The SRM size can be well controlled from 4 μm to 50 μm by adjusting the flow rates of the inner and the outer liquid phases. The acoustic and the optical droplet vaporization processes of the SRMs were demonstrated in benchtop experiments. Upon acoustic stimulation by a therapeutic ultrasound transducer at 1 MHz and 1 W cm −2, the SRMs were activated and the induced echogenicity was monitored by clinical ultrasonography. Upon optical stimulation by a 445 nm laser beam at power intensity larger than 35 W cm −2, the SRMs were activated and the volume expansion of the SRMs was monitored by bright field microscopy. Our benchtop experiments demonstrated the technical feasibility for acoustic and optical mediation of the SRMs. The technique can be potentially used for multiple therapeutic applications such as thermal ablation, vascular occlusion, and locoregional drug delivery.